From being to doing teacher: socio-demographic reconstruction of the educational fact - Claret Escalona, Mary (2017)
This article has like a purpose to project the social semiotic reconstruction of the educative reality since the meanings and senses that teachers from educative institutions of medium education from Barquisimeto city in Venezuela, assigned. The study was located in the qualitative approach of the interpretative paradigm, observed since the phenomenological and hermeneutic. Through the deep interview, oral discourses from social actors were obtained; they were selected in an open and flexible way. Adopting an emergent and creative design, it was done a hermeneutic analysis where different categories were obtained, categories such as: the vision of being a teacher; the fate of being a teacher in time; the called vocation to be a teacher in the practice; mirrors to project oneself; building the image of a teacher; the spiritual posture of a teacher among other. In a reflecting way, this study configure different intern landscapes of the teachers to help us to understand why is so important to explore the being of a professional, its practice, exalting the teacher condition, that in this time of crisis and incertitude that Latin America and special Venezuela live.